Liberia's First Health Workforce Program Strategy: Reflections and Lessons Learned - Bernice Dahn; Lila Kerr; Tej Nuthulaganti; Moses Massaquoi; Marion Subah; Attila Yaman; Chelsea M. Plyler; Corrado Cancedda; Roseda E. Marshall; Regan H. Marsh (Ubiquity Press, 2021)
Following civil war and the Ebola epidemic, Liberia's health workforce was devastated, essential health services and primary care were disrupted, and health outcomes for maternal and child mortality were amongst the worst in the world. To reverse these trends, the government of Liberia developed the 'Health Workforce Program (HWP) Strategy 2015-2021'. With the goal of building a resilient and responsive health system to ensure access to essential services and the ability to respond to future crises, this strategy aimed to add 6,000 new professionals to the workforce. In the context of the COVID-19 pandemic, we share lessons learned from the program's development and first years of implementation.